2017
DOI: 10.1002/hep.29005
|View full text |Cite
|
Sign up to set email alerts
|

Eight weeks of ledipasvir/sofosbuvir is effective for selected patients with genotype 1 hepatitis C virus infection

Abstract: An 8-week duration of treatment with LDV/SOF is highly effective in properly selected patients; greater use of this regimen is recommended. (Hepatology 2017;65:1094-1103).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 23 publications
9
44
0
Order By: Relevance
“…These results are similar to those reported in the ION‐3 trial, in which 215 patients received SOF/LDV for 8 weeks, with an SVR rate of 94% and a relapse rate of 5% . Real‐world cohort data have also shown the comparable effectiveness of SOF/LDV for 8 and 12 weeks in HCV genotype 1–infected, treatment‐naive patients without cirrhosis . Of note, the proportions of patients with METAVIR F3 fibrosis (or an equivalent by transient elastography) treated with SOF/LDV for 8 weeks were 13% in the ION‐3 trial and <25% in Madrid‐CoRe.…”
Section: Discussionsupporting
confidence: 83%
“…These results are similar to those reported in the ION‐3 trial, in which 215 patients received SOF/LDV for 8 weeks, with an SVR rate of 94% and a relapse rate of 5% . Real‐world cohort data have also shown the comparable effectiveness of SOF/LDV for 8 and 12 weeks in HCV genotype 1–infected, treatment‐naive patients without cirrhosis . Of note, the proportions of patients with METAVIR F3 fibrosis (or an equivalent by transient elastography) treated with SOF/LDV for 8 weeks were 13% in the ION‐3 trial and <25% in Madrid‐CoRe.…”
Section: Discussionsupporting
confidence: 83%
“…Rates of virologic breakthrough (reappearance of HCV RNA while on therapy) or relapse (reappearance of HCV RNA after completion of therapy) were low in all four studies, ranging from 0%–6% 31. These findings have been corroborated in several large real-world observational and registry studies ranging from 600 to 14,000 patients 3240. The efficacy of LDV/SOF for treating adults with CHC from other genotypes has also been supported by multiple Phase II trials,4147 a Japanese Phase III trial, and real-world data from a French cohort 31…”
Section: Ldv/sof Use In Adultssupporting
confidence: 66%
“…Our study showed that the percentage of inmates undergoing 8‐week treatment courses was lower than in the general population (0.5% vs 10.5%). Studies that have demonstrated the efficacy of shorter therapies in selected populations without cirrhosis indicate the need to reduce courses of treatment. What is more, the introduction of new drugs such as voxilaprevir, glecaprevir and pibrentasvir in the near future will facilitate the use of these shorter therapies and may be able to avoid the abandonment of treatment among inmates when they are released …”
Section: Discussionmentioning
confidence: 99%